Odškodnina za izgubljeni dopust v domači sodni praksi - Zupan, Nina (Pravni letopis, 2016)
Following the ruling of the European Court of Justice in the "Leitner v. TUI" case, which is a binding legal source for the EU member states, compensation for non-material damage arising from the loss of enjoyment of the holiday is now also acklowledged in Slovenia. The Supreme Court of the Republic of Slovenia has held that further legislative changes are not necessary in order to assure the compatibility of national law with the Council Directive 90/314/EEC on package travel, package holidays and package tours, since it can be assured by the interpretation of the existing legislation in conformity with the EU law. However, numerous issues relating to compensation claims may arise due to deficient implementation of the Directive. Legislative changes could, therefore, be contemplated for reasons of legal certainty. Another particular challenge to be resolved in case-law is assessment of the amount of damages.
Keywords: dopust; kršenje; nepremoženjska škoda; odškodnina; odškodninsko pravo; pogodbe